2013
DOI: 10.1002/ajoc.201300017
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of ArSSAr to Alkenes: The Implications of a Cationic Chain Mechanism Initiated by Electrogenerated ArS(ArSSAr)+

Abstract: The addition reactions of diaryl disulfides (ArSSAr) to alkenes and alkynes were achieved with a catalytic amount of an arylbis(arylthio)sulfonium ion (ArS(ArSSAr)+), which was generated and accumulated by low‐temperature electrolysis of ArSSAr, to give the corresponding diarylthiolated products. The electrolysis of a mixture of ArSSAr and an alkene with a catalytic amount of electricity was also effective to drive the reactions. A cation chain mechanism mediated by ArS(ArSSAr)+ as a chain carrier is suggested. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Catalytic protocols have also been developed wherein substoichiometric amounts of the ArS + equivalent initiates a cation chain mechanism. 507,508 This “ArS + cation pool” also found utility in the functionalization of arenes, allyl silanes, enol ethers, and ketene acetals (Figure 33B, middle); 511 moreover, it could be used to induce oxocarbenium formation through reaction with thioacetals (Figure 33B, right). 512514 This process has found application in glycosylation chemistry where efficient protocols with flow reactors have been detailed.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Catalytic protocols have also been developed wherein substoichiometric amounts of the ArS + equivalent initiates a cation chain mechanism. 507,508 This “ArS + cation pool” also found utility in the functionalization of arenes, allyl silanes, enol ethers, and ketene acetals (Figure 33B, middle); 511 moreover, it could be used to induce oxocarbenium formation through reaction with thioacetals (Figure 33B, right). 512514 This process has found application in glycosylation chemistry where efficient protocols with flow reactors have been detailed.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…45 On the other hand if BF 4 is used as the counteranion, the reaction requires a stoichiometric amount of ArS (ArSSAr) . In the former case the reaction seems to proceed by the cation chain mechanism shown in Scheme 22.…”
Section: Cyclization Of Dienes Using Arsmentioning
confidence: 99%
“…[19][20][21] We have reported that the electrochemical oxidation of diaryl disulfides (ArSSAr) leads to the formation of ArS(ArSSAr) + , which can be accumulated in solution at low temperatures ( Figure 1). [22][23][24][25][26] This reaction presumably proceeds by generation of "ArS + " followed by its reaction with ArSSAr. Therefore, we envisaged that the anodic oxidation of ArSSAr in the presence of alkynes leads to the formation of thiirenium ions ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%